Gains and pains: a qualitative study on the implications of value-based health care for professionals - Veerle van Engen; Igna Bonfrer; Fabio Mieris; Malou Ensink; Anne Stiggelbout; Kees Ahaus; Martina Buljac-Samardzic (Human Resources for Health)
Abstract Background While aiming to optimize patient value, the shift towards Value-Based Health Care (VBHC) in hospitals worldwide has been argued to benefit healthcare professionals as well. However, robust evidence regarding VBHC’s workforce implications is lacking. This gap is problematic, as the motivation and health of healthcare professionals are central to the quality of care and crucial amidst contemporary workforce challenges. This study aims to qualitatively examine the implications of VBHC for healthcare professionals’ motivation, job strain, and ongoing participation in VBHC. In addition, it explores how these outcomes are regulated at both the individual and organizational levels. Methods Semi-structured interviews were conducted with 26 healthcare professionals across six Dutch hospitals. Interviewees engaged in three VBHC activities: (1) value-based outpatient consultations and/or; (2) value-based quality improvement activities; as well as in; (3) VBHC implementation. Interview questions and data analysis were guided by the Job Demands–Resources model. Results VBHC interacts with four themes perceived to affect professional’s motivation (perception of making a positive impact, enjoyability of job activities, personal development, and sense of community and support) and three themes perceived to affect job strain (workload, cognitive demands, and confidence). VBHC creates both gains (primarily increasing motivation; occasionally reducing strain) and pains (primarily increasing strain; sometimes reducing motivation). The perceived impact of VBHC depends on the fit between the individual, one’s activities in VBHC, the working conditions, and the pace of VBHC implementation. An observation that warrants attention is that healthcare professionals with a 'do-er' mentality and high ambitions to optimize patient value can become demotivated to continue advancing VBHC with the same intensity, particularly due to perceived slow progress. Conclusions While VBHC is centered around patients, this study emphasizes that the needs, experiences and changing role identities of healthcare professionals cannot be overlooked in this transition. VBHC currently presents as a double-edged sword for healthcare professionals: resulting in both gains and pains. In the move to VBHC, it is crucial to maintain alignment between the individual, their job activities, the work environment, and the pace at which VBHC unfolds. This is essential for fostering and retaining motivated individuals, who are not only vital to the workforce but also pivotal in advancing VBHC.